1995
DOI: 10.1152/ajpcell.1995.269.5.c1140
|View full text |Cite
|
Sign up to set email alerts
|

Warming macrophages to febrile range destabilizes tumor necrosis factor-alpha mRNA without inducing heat shock

Abstract: We have previously reported that sustained tumor necrosis factor (TNF)-alpha expression is suppressed by temperatures in the febrile range in human macrophages. In this study, we examined the mechanisms of high-temperature-induced macrophage TNF suppression in the RAW 264.7 macrophage cell line. Incubating lipopolysaccharide (LPS)-stimulated RAW 264.7 cells at 40 degrees C reduced TNF secretion by 92% and peak TNF mRNA levels by 43% compared with cells incubated at 37 degrees C (P < 0.05) but did not affect le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
2
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
9
38
2
1
Order By: Relevance
“…These data suggest that febrile core temperature is predominantly suppressive for TNF-␣ expression during bacterial infections. This finding in the febrile animals is consistent with the early deactivation of TNF-␣ gene expression in macrophages in vitro previously reported by our laboratory (11,12,18), an effect caused by destabilization of TNF-␣ mRNA (11), and an early cessation of transcription (21a). The latter effect is mediated in part by partial activation of heat shock factor 1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data suggest that febrile core temperature is predominantly suppressive for TNF-␣ expression during bacterial infections. This finding in the febrile animals is consistent with the early deactivation of TNF-␣ gene expression in macrophages in vitro previously reported by our laboratory (11,12,18), an effect caused by destabilization of TNF-␣ mRNA (11), and an early cessation of transcription (21a). The latter effect is mediated in part by partial activation of heat shock factor 1.…”
Section: Discussionsupporting
confidence: 91%
“…Mean Ϯ SE; n ϭ 6; ‫,ء‬ P Ͻ 0.05 compared with the "no fever" mice. (11,12,18). We also reported that increasing core temperature in LPS-challenged mice accelerated and enhanced an early, self-limited pulse of TNF-␣ in plasma but subsequently suppressed persistent TNF-␣ expression and enhanced the expression of IL-6 (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…We showed that exposing RAW cells to 39.5°C for 2-4 h increased Hsp70 mRNA levels 7-15-fold. In an earlier study, we found that exposing RAW cells to 40°C failed to activated Hsp70 mRNA expression (45), but the cells were only heated for 30 min in the previous study. The results of the two studies are consistent with our observation that Hsp70 induction at less extreme hyperthermia requires longer exposure time (27).…”
Section: Discussionmentioning
confidence: 77%
“…This suggests that macrophages and/or neutrophils are the critical cell type that must regulate TNF-␣ production during a fever response in order to prevent septic shock. In fact, the Hasday group showed that transcription of TNF-␣ was inhibited in a variety of different monocyte and macrophage cell types exposed to physiologic fever temperature (39.5°C) and that this transcriptional regulation was dependent on HSF1 (9,10,37).…”
Section: Discussionmentioning
confidence: 99%